2022
DOI: 10.3389/fnmol.2022.831825
|View full text |Cite
|
Sign up to set email alerts
|

Hyperacute Excitotoxic Mechanisms and Synaptic Dysfunction Involved in Traumatic Brain Injury

Abstract: The biological response of brain tissue to biomechanical strain are of fundamental importance in understanding sequela of a brain injury. The time after impact can be broken into four main phases: hyperacute, acute, subacute and chronic. It is crucial to understand the hyperacute neural outcomes from the biomechanical responses that produce traumatic brain injury (TBI) as these often result in the brain becoming sensitized and vulnerable to subsequent TBIs. While the precise physical mechanisms responsible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 105 publications
(148 reference statements)
0
15
0
Order By: Relevance
“…TBI can be divided into four phases: hyperacute (minutes to hours), acute (hours to several days), subacute (several days to weeks), and chronic (months and beyond) [ 56 ]. Our results showed that during the hyperacute phase (30 min to 12 h postinjury), the cellular activity of microglia in the injury group was significantly lower than in the sham group, while in the acute phase (1 day to 3 days postinjury) the difference was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…TBI can be divided into four phases: hyperacute (minutes to hours), acute (hours to several days), subacute (several days to weeks), and chronic (months and beyond) [ 56 ]. Our results showed that during the hyperacute phase (30 min to 12 h postinjury), the cellular activity of microglia in the injury group was significantly lower than in the sham group, while in the acute phase (1 day to 3 days postinjury) the difference was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…The processes underlying TBI-induced excitotoxicity begin within seconds of the initial trauma, with dysfunction of the cell membrane and ion channels leading to increased intracellular calcium ([Ca 2+ ]i) [25]. This increase in [Ca 2+ ]i triggers release of vesicles containing neurotransmitters including glutamate into the synaptic cleft as early as 30 minutes following TBI [25]. Excess glutamate stimulates NMDA and AMPA receptors on nearby neurons, triggering depolarization and increased [Ca 2+ ]i that propagates a wave of excess excitation [26].…”
Section: Anti-excitatory Treatmentsmentioning
confidence: 99%
“…Excess glutamate stimulates NMDA and AMPA receptors on nearby neurons, triggering depolarization and increased [Ca 2+ ]i that propagates a wave of excess excitation [26]. While this excitation is initially tolerable to neurons, mitochondrial failure begins to occur within four hours of trauma, leading to energy depletion, neuronal apoptosis and neurodegeneration [25]. These alterations in [Ca 2+ ]i have been observed to persist up to seven days after TBI, in association with neuronal dysfunction [27].…”
Section: Anti-excitatory Treatmentsmentioning
confidence: 99%
“…Reported mathematical models of brain-scale blast-induced biomechanics can predict local brain tissue stress-strain profiles ( Gupta et al, 2017 ). However, in spite of large volume of work on mathematical modeling of synaptic, axonal and neuronal neurotransmission, metabolism and signaling pathways very little has been reported on modeling synaptic mechanobiology ( Przekwas et al, 2016 ; Hall et al, 2021 ; Keating and Cullen, 2021 ; Hoffe and Holahan, 2022 ; Procès et al, 2022 ). In the present paper we introduce an initial formulation of a computational model of a mechanobiological “response” of a neuronal synapse to acute and repeated sub-concussive blast loads.…”
Section: Introductionmentioning
confidence: 99%